Encephalitozoon cuniculi antibodies in a specific-pathogen-free rabbit unit. - Bywater, J E (1978)
We describe our discovery of Encephalitozoon cuniculi antibodies in a specific-pathogen-free rabbit colony. Small-sized samples had failed to reveal the presence of infection with a prevalence of about 5%. Using an India ink immunoreaction test by which we were able to visualize both negative and positive reactions, we were able to undertake a 100% screen of the colony of more than 700 rabbits and to repeat this 4 weeks later when we had culled the positive reactors. By collating the results of those tests with the results of tests on previously collected samples, we have been able to discuss and observe age and sex susceptibilities and the mode of transmission of the naturally occurring disease.